2015
DOI: 10.1038/bmt.2015.278
|View full text |Cite
|
Sign up to set email alerts
|

Impact of conditioning with TBI in adult patients with T-cell ALL who receive a myeloablative allogeneic stem cell transplantation: a report from the acute leukemia working party of EBMT

Abstract: on behalf of the Acute Leukemia Working Party of EBMT Allogeneic hematopoietic stem cell transplantation (allo-SCT) is a therapeutic option for adult patients with T-cell ALL (T-ALL). Meanwhile, few allo-SCT data specific to adult T-ALL have been described thus far. Specifically, the optimal myeloablative conditioning regimen is unknown. In this retrospective study, 601 patients were included. Patients received allo-SCT in CR1, CR2, CR 42 or in advanced disease in 69%, 15%, 2% and 14% of cases, respectively. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
42
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 32 publications
8
42
2
Order By: Relevance
“…There still is uncertainty regarding the optimal conditioning regimen in patients with ALL. Our observations are in keeping with the results of several published trials suggesting the superiority of TBI‐containing regimens . Although in the most recent of these studies intravenous busulfan was the most common chemotherapy‐only regimen, some doubts remain regarding whether the intravenous administration could eliminate the survival advantages of TBI in patients with ALL as appears to be the case in patients with PREF AML …”
Section: Discussionsupporting
confidence: 87%
“…There still is uncertainty regarding the optimal conditioning regimen in patients with ALL. Our observations are in keeping with the results of several published trials suggesting the superiority of TBI‐containing regimens . Although in the most recent of these studies intravenous busulfan was the most common chemotherapy‐only regimen, some doubts remain regarding whether the intravenous administration could eliminate the survival advantages of TBI in patients with ALL as appears to be the case in patients with PREF AML …”
Section: Discussionsupporting
confidence: 87%
“…Survival also was better in patients undergoing HCT in CR1 compared to ≥CR2, with better survival in patients age <35 years receiving a TBI-based MAC regimen compared with those receiving a busulfan- or cyclophosphamide-based MAC regimen [5]. Although we observed no impact of specific conditioning regimen on survival, we also verified that the use of TBI in this disease was associated with better survival.…”
Section: Discussionsupporting
confidence: 66%
“…As shown in Bu/Cy radiation-free conditioning in terms of LFS and OS. 17 In the same vein, a recent analysis undertaken by the EBMT in more than 4000 ALL patients also indicated that the use of TBI-based conditioning led to a reduced risk of relapse as well as treatment failure. 18 In our current analysis, we aimed to determine whether thiotepa- 19 While admittedly this was a small cohort of patients, it is however important to note that these were patients with relapsed disease who were able to achieve an impressive 3-year OS rate of 49% following thiotepa-based conditioning further underscoring the potent anti-leukemia activity attainable with this preparative radiation-free regimen.…”
Section: Multivariate Analysis For Patients In Cr1mentioning
confidence: 98%